P The Role Of Agriculture sector on economic Growth Of The Province Of Southeast Sulawesi C0vid-19 Pandemic TIME - Nurcayah Nurcayah; Syamsinar; Basri; Muhammad (Fakultas Pertanian Universitas Muhammadiyah kendari, 2022)
The aim of the study was to determine the performance of the agricultural sector on economic growth in Southeast Sulawesi Province during the Covid-19 pandemic, to determine the role of the agricultural sector in Southeast Sulawesi's economic growth. The data used in this research is secondary data. The analysis used is descriptive. Tests used in the LQ and DLQ Analysis models. Research results The performance of the agricultural sector during the covid-19 pandemic in Quarter I and Quarter II the agricultural sector grew positively even though it experienced a slowdown due to some areas having harvest season, demand for agricultural products began to decline due to social restriction policies at the beginning of the pandemic, especially fisheries so that fishermen reduced their operations quarter III - IV the growth rate of the agricultural sector contracted due to drastic decline in fishery production and decreased rice crop production due to weather factors and pests and diseases. . The results showed that the LQ value was 1.76 > 1 and the DLQ was 0.13 < 1, meaning that the role of the agricultural sector in Southeast Sulawesi Province based on and has potential for future development